EPIDEMIOLOGY OF SCORPION ENVENOMATION IN THE STATE OF CEARÁ, NORTHEASTERN BRAZIL - FURTADO, Sanny da Silva; BELMINO, José Franscidavid Barbosa; DINIZ, Ana Gilza Quaresma; LEITE, Renner de Souza (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
This report is a retrospective study of the epidemiology of scorpion sting cases recorded from 2007 to 2013 in the State of Ceará, Northeastern Brazil. Data were collected from the Injury Notification Information System database of the Health Department of Ceará. A total of 11,134 cases were studied and distributed across all the months of the studied period and they occurred mainly in urban areas. Victims were predominantly 20-29 years-old women. Most victims were bitten on the hand; and received medical assistance within 1-3 hours after being bitten. Cases were mostly classified as mild and progressed to cure. Scorpion envenomation in Ceará is an environmental public health problem that needs to be monitored and controlled throughout the year.